Promoted hydrogen generation from formic acid with amines using Au/ZrO2 catalyst. (14th December 2016) - Bi, Qing-Yuan; Lin, Jian-Dong; Liu, Yong-Mei; Huang, Fu-Qiang; Cao, Yong
Abstract: Decomposition of formic acid (FA) to hydrogen and carbon dioxide through catalysis holds great promise for clean energy in fuel cells designed for portable use, but the selective and efficient dehydrogenation of FA by a robust heterogeneous catalyst under ambient conditions remains a major challenge. We report herein that a new FA dehydrogenation system comprising liquid FA and amines with high boiling point as hydrogen storage material can be efficiently decomposed for ultrapure H2 release under mild reaction conditions. Of significant importance is that a high turnover frequency (TOF) of up to 1166 h −1 can be readily attained at 60 °C in FA-dimethylethanolamine system using gold nanoparticles supported on amphoteric zirconia (Au/ZrO2 ). The amine acts as a proton scavenger can facilitate the OH bond cleavage in the key step of FA deprotonation in Au–ZrO2 interface resulting in high catalytic activity. The versatile gold catalyst displayed excellent stability for dimethylethanolamine-assisted FA dehydrogenation as well as a typical particle-size-dependent effect. Graphical abstract: Highlights: Amine acts as a proton scavenger can facilitate the cleavage of OH bond of HCOOH. Dimethylethanolamine with high boiling point shows the most promoting effect. Au/ZrO2 exhibits excellent catalytic activity of 1166 h −1 at 60 °C. Gold displays a typical particle-size-dependent effect for HCOOH dehydrogenation.